Identifying PM2.5-bound metal pollution sources in Southern Thailand using positive matrix factorization and principal component analysis - Siwatt Pongpiachan; Sarunpron Khruengsai; Teerapong Sripahco; Radshadaporn Janta; Rungruang Janta; Jompob Waewsak; Danai Tipmanee; Saran Poshyachinda; Patcharee Pripdeevech (Atmospheric Environment: X)
This study presents the first integrated source apportionment and health risk assessment of PM2.5-bound metals in Southern Thailand using Positive Matrix Factorization (PMF) and Principal Component Analysis (PCA). PM2.5 samples were collected across three urban-industrial provinces, Nakhon Si Thammarat (NST), Phuket (PKT), and Songkhla (SKA), during multiple months in 2023. PMF successfully resolved five major emission sources, including industrial processes, vehicular traffic, maritime fuel combustion, waste incineration, and fossil fuel combustion, explaining 58.4 % of the variance in the dataset. PCA offered complementary insight but lacked the resolution to isolate mixed-source tracers such as vanadium (V) and nickel (Ni), with lower total explained variance. Metal concentrations and source contributions exhibited distinct spatial and seasonal patterns, reflecting dynamic emission influences across the region. Phuket emerged as a hotspot for toxic metal exposure, with the highest hazard index (HI = 1.63) and cancer risk (4.79 × 10−4), exceeding international safety thresholds. In contrast, NST showed elevated Zn and Ag from traffic-related sources, while SKA was dominated by V and Ni from maritime emissions. Enrichment factor analysis further highlighted anthropogenic signatures, with exceptionally high values for Hg (Log EF = 6.09) in PKT and arsenic (As) (39 % of total metal mass) in SKA. Our findings provide new regional-scale evidence of metal-specific health risks and emission patterns in an understudied Southeast Asian context. This work supports the urgent need for strengthened regulatory policies targeting industrial and vehicular emissions, improved waste management, and expanded air quality monitoring to mitigate public health impacts from PM2.5-bound metals in Southern Thailand.